Evaluation of oncofertility care in childhood cancer patients: the EU-Horizon 2020 twinning project TREL initiative - Stukaite-Ruibiene, Egle; van der Perk, M. E. Madeleine; Vaitkeviciene, Goda Elizabeta; Bos, Annelies M. E.; Bumbuliene, Zana; van den Heuvel-Eibrink, Marry M.; Rascon, Jelena (Frontiers in Pediatrics, 2023)
Background. The five-year survival rate of childhood cancer exceeds 80%, however, many survivors develop late effects including infertility. The aim of this study was to evaluate the current status of oncofertility care at Vilnius University Hospital Santaros Klinikos (VULSK) within the framework of the EU-Horizon 2020 TREL project.Methods. All parents or patients aged 12-17.9 years treated from July 1, 2021 until July 1, 2022 were invited to complete an oncofertility-care-evaluation questionnaire. After completing the questionnaire, patients were triaged to low-risk (LR) or high-risk (HR) of gonadal damage using a risk stratification tool (triage). Data was assessed using descriptive statistics.Results. Questionnaires were completed by 48 parents and 13 children triaged as 36 (59%) LR and 25 (41%) HR patients. Most HR respondents (21/25, 84%) were not counseled by a fertility specialist. Six boys (4 HR, 2 LR) were counseled, none of the girls was counseled. Three HR boys underwent sperm cryopreservation. Only 17 (27.9%, 9 HR, 8 LR) respondents correctly estimated their risk. All counseled boys (n=6) agreed the risk for fertility impairment had been mentioned as compared to 49.1% (n=27) of uncounseled. All counseled respondents agreed they knew enough about fertility (vs 42%).Respondents counseled by a fertility specialist were provided more information on fertility than uncounseled. HR patients were not sufficiently counseled by a fertility specialist. Based on the current experience oncofertility care at VULSK will be improved.